2008
DOI: 10.1152/ajpregu.00659.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin mix levels influence the ossification process in European sea bass (Dicentrarchus labrax) larvae

Abstract: The influence of dietary vitamins on growth, survival, and morphogenesis was evaluated until day 38 of posthatching life in European sea bass larvae (Dicentrarchus labrax). A standard vitamin mix (VM), at double the concentration of the U.S. National Research Council's recommendations, was incorporated into larval feeds at 0.5%, 1.5%, 2.5%, 4.0%, and 8.0% to give treatments VM 0.5, VM 1.5, VM 2.5, VM 4.0, and VM 8.0, respectively. The group fed the VM 0.5 diet all died before day 30. At day 38, the larvae grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 28 publications
5
50
0
1
Order By: Relevance
“…This mechanism still needs to be elucidated. Nonetheless, our transcriptomic analyses showed that the expression pattern of osteocalcin, a marker of bone differentiation and mineralization (Mazurais et al 2008; Darias et al 2010a), was not affected by ambient . This suggests that the observed faster skeletogenesis may be an indirect effect of internal pH homeostasis, rather than the result of a specific calcification regulatory pathway.…”
Section: Discussionmentioning
confidence: 72%
“…This mechanism still needs to be elucidated. Nonetheless, our transcriptomic analyses showed that the expression pattern of osteocalcin, a marker of bone differentiation and mineralization (Mazurais et al 2008; Darias et al 2010a), was not affected by ambient . This suggests that the observed faster skeletogenesis may be an indirect effect of internal pH homeostasis, rather than the result of a specific calcification regulatory pathway.…”
Section: Discussionmentioning
confidence: 72%
“…Previously, it has been shown that both bone/cartilage ratio and mineralization patterning coincide with regulation of osteocalcin gene expression (Bensimon-Brito et al, 2012;Mazurais et al, 2008).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Varsamos et al 2006, Terova et al 2007, Mazurais et al 2008), as they retrieved, e.g., better repeatability of C q values and efficiencies (details not reported). GHR expression was not previously investigated in sea bass.…”
Section: Reverse Transcription and Quantitative Real-time Polymerase mentioning
confidence: 89%